2015
DOI: 10.1038/bjc.2015.173
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of BRAF mutation as a predictive biomarker of benefit from anti-EGFR monoclonal antibody therapy for RAS wild-type metastatic colorectal cancer

Abstract: Background:Metastatic colorectal cancer (mCRC) that harbours a BRAF V600E mutation (BRAF MT) is associated with poorer outcomes. However, whether this mutation is predictive of treatment benefit from anti-epidermal growth factor receptor (EGFR) monoclonal antibodies (mAbs) is uncertain.Methods:We conducted a systematic review and meta-analysis of randomised controlled trials (RCTs) published up to July 2014 that evaluated the effect of BRAF MT on the treatment benefit from anti-EGFR mAbs for mCRC.Results:Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
193
2
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(207 citation statements)
references
References 33 publications
1
193
2
11
Order By: Relevance
“…However, the test of interaction (p = 0.43) was not statistically significant, highlighting the possibility that the observed differences in the effect of anti-egfr mAbs on os according to the BRAF mutation status might be attributable to chance alone. With respect to the pfs benefit with anti-egfr mAbs, the hr was 0.86 (95% ci: 0.61 to 1.21) for RAS wt, BRAF-mutant tumours and 0.62 (95% ci: 0.50 to 0.77) for RAS wt, BRAF wt tumours (test of interaction, p = 0.07) 87 .…”
Section: Evidence Summarymentioning
confidence: 96%
See 2 more Smart Citations
“…However, the test of interaction (p = 0.43) was not statistically significant, highlighting the possibility that the observed differences in the effect of anti-egfr mAbs on os according to the BRAF mutation status might be attributable to chance alone. With respect to the pfs benefit with anti-egfr mAbs, the hr was 0.86 (95% ci: 0.61 to 1.21) for RAS wt, BRAF-mutant tumours and 0.62 (95% ci: 0.50 to 0.77) for RAS wt, BRAF wt tumours (test of interaction, p = 0.07) 87 .…”
Section: Evidence Summarymentioning
confidence: 96%
“…Advances in molecular biology since the late 1990s have helped to identify and understand the mechanism of colorectal carcinogenesis. In metastatic crc, egfr and the downstream mapk pathways play a major role in disease progression and have led to the development of multiple targeted therapies 87 . Colorectal cancer can be classified according to molecular markers.…”
Section: Evidence Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…[4,5] It has been hypothesised that poor outcomes are secondary to intrinisc chemoresistance but there is a paucity of data describing the outcomes of Bmutant aCRC with chemotherapy alone, particularly beyond the firstBline. This is particularly important as B mutant patients have questionable benefit from antiBepidermal growth factor receptor (antiBEGFR) therapies [6] and Btargeted strategies have yet to make clinical impact in aCRC. [7,8] Importantly previous publications have not performed careful multivariate analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Nor was there sufficient evidence to identify a statistically significant benefit to this treatment. 55 A second meta-analysis showed that EGFR monoclonal antibody treatment in patients whose tumors contain a BRAF p.V600 mutation was not associated with significant OS (P ¼ .43), although there was a trend for better PFS (P ¼ .07).…”
mentioning
confidence: 99%